Ultrasonic pretreatment prior to Soxhlet extraction for essential oil from basil leaves (Ocimum basilicum L.) - Muzaiyin, Nuramanina; Hamzah, Muhammad Hazwan; Che Man, Hasfalina (Malaysian Society of Agricultural Engineers, 2019)
The extraction of oil from basil leaves was investigated by using conventional Soxhlet extraction method and ultrasonic as a pre-treatment prior to Soxhlet extraction. The effects of two operating parameters on the oil extraction namely solvent to solid ratio and reaction time were investigated to optimize the processing conditions of conventional Soxhlet extraction for achieving maximum oil yield using Response Surface Methodology (RSM). The optimum conditions were found at 5 hours, and a solvent to solid ratio of 1:33. The oil recovery from ultrasonic pretreatment prior to Soxhlet extraction under the same optimum parameters was compared. The yield of oil from samples underwent ultrasonic as a pretreatment was 4.14% while the conventional Soxhlet method yielded 6.24%. This finding is consistent with the evidence of Scanning Electron Microscopy (SEM) images showed that the treated samples were flakier and porous than untreated samples. Overall, this study has shown that treated samples via ultrasonic is incapable to increase the oil yield percentage compared to the conventional Soxhlet extraction method.